2019
DOI: 10.1039/c9nj00411d
|View full text |Cite
|
Sign up to set email alerts
|

Phosphorus-doped molybdenum disulfide facilitating the photocatalytic hydrogen production activity of CdS nanorod

Abstract: Phosphorus doping could modulate the band structure and hydrogen evolution reaction over potential, and bring about the excellent photocatalytic hydrogen evolution activity of CdS/P-MoS2.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 32 publications
0
5
0
Order By: Relevance
“…The Cd 3 d 3/2 peak at 411.54 eV had atomic content of 21.58% before bio-sorption. The weaker P 2 p 1/2 peaks at 131.99 eV, 134.39 eV, 138.05 eV, 139.46 eV, 139.95 eV, and 144.32 eV correspond to P–O–C or P–O species before bio-sorption 90 . The occurrence of the P 2 p peaks at 136.50 eV and 139.46 eV corresponds to the formation of phosphorous-Cd 2+ ions after adsorption 90 .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The Cd 3 d 3/2 peak at 411.54 eV had atomic content of 21.58% before bio-sorption. The weaker P 2 p 1/2 peaks at 131.99 eV, 134.39 eV, 138.05 eV, 139.46 eV, 139.95 eV, and 144.32 eV correspond to P–O–C or P–O species before bio-sorption 90 . The occurrence of the P 2 p peaks at 136.50 eV and 139.46 eV corresponds to the formation of phosphorous-Cd 2+ ions after adsorption 90 .…”
Section: Resultsmentioning
confidence: 99%
“…The weaker P 2 p 1/2 peaks at 131.99 eV, 134.39 eV, 138.05 eV, 139.46 eV, 139.95 eV, and 144.32 eV correspond to P–O–C or P–O species before bio-sorption 90 . The occurrence of the P 2 p peaks at 136.50 eV and 139.46 eV corresponds to the formation of phosphorous-Cd 2+ ions after adsorption 90 . The biogeochemistry of heavy metals can easily be understood from the binding mechanisms of Cd 2+ ion by the resistant strain Candida tropicalis XTA1874.…”
Section: Resultsmentioning
confidence: 99%
“…To date, many metal sulfides, such as MoS2 [30,[184][185][186][187][188], NiS [45,51,184,189], CuxS [190][191][192][193][194][195][196], Co3S4 [197], FeS [198], Ag2S [199], Bi2S3 [200], WS2 [201], Co3Mo7S [15] and NiMoS [202,203], have been reported in photocatalytic H2 evolution reaction. MoS2 is an efficient cocatalyst on variety of semiconductor photocatalysts.…”
Section: Metal Sulfidesmentioning
confidence: 99%
“…Very recently, Xu et al [188] found that MoS2 could be facilely modulated through phosphorus doping, which can act as a cocatalyst and embedded onto the CdS nanorod for not only facilitating the separation of the charge carriers, but also promoting the separation efficiency of the charge carriers. The 3 wt.% CdS/P-MoS2 sample exhibited a higher photocatalytic hydrogen evolution rate of 8.86 mmol•h -1 •g -1 with the AQY of 32.4% at 420 nm.…”
Section: Metal Sulfidesmentioning
confidence: 99%
“…Renewable hydrogen generation from photocatalytic water splitting has been reckoned as a green and effective development strategy to alleviate the environmental pollutant and energy crisis. A large number of semiconductors such as TiO 2 , CdS, carbon nitride, metal–organic frameworks (MOFs), and so on. have been reported for hydrogen generation .…”
Section: Introductionmentioning
confidence: 99%